Hysteroscopic resectoscope-directed biopsies and outpatient endometrial sampling for assessment of tumor histology in women with endometrial cancer or atypical hyperplasia. (August 2020) - Dueholm, M.; Hjorth, I.M.D.; Dahl, K.; Ørtoft, G.
Highlights: Endometrial cancer is frequent in outpatient endometrial samples with atypical hyperplasia. Hysteroscopic resectoscope-directed biopsies may differentiate cancer and atypical hyperplasia. Efficacious outpatient endometrial samples with a diagnosis of tumor type and grade is reliable. Abstract: Objective: To evaluate and compare the diagnostic efficiency of outpatient endometrial sampling (OES) and hysteroscopic resectoscope-directed biopsies (HYbiopsy ) to distinguish between endometrial cancer (EC) and atypical hyperplasia (AH) and to assess tumor type and grade (histotype) in women with EC. Design: Patients with AH or EC ( n = 266) among 1013 patients consecutively referred because of postmenopausal bleeding were included. Identification of EC versus AH, and unfavorable tumor types (endometrioid grade 3 or non-endometrioid tumors) using OES and HYbiopsy was compared to final histopathology at hysterectomy. AH or EC were identified by OES in 184 patients and by HYbiopsy in212. Results: OES had only sufficient tissue samples in 72.7% of intended samples. Even when OES did provide sufficient material, addition of HYbiopsy was a better technique than OES alone to distinguish between EC and AH, with an AUC of 95.9% and 79.8%; sensitivity of 97.4% and 64.6% and a specificity of 94.4% and 95.0%, respectively ( p = 0.008). AH was falsely diagnosed with OES in 58 (35.4%) of 164 women with a final diagnose of EC. A final diagnosis of stage 1b or more was seen in 22 of these 58 women, while 5 of 194 patients with EC all stage 1a grade 1 had AH by HYbiopsy . HYbiopsy had higher correlation in assessment of tumor type and grade than OES, but OES and HYbiopsy had comparable AUC of 90.3% and 92.4% for identification of unfavorable tumors when tumor histotype was successfully identified. Regarding identification of unfavorable tumors ( n = 57), a successfully assessment of histotype by OES combined with HYbiopsy in women without successfully diagnosed histotype by OES alone had AUC of 91.3%. Conclusion: Addition of HYbiopsy may improve diagnosis when preoperative OES identifies AH or is insufficient for explicit diagnosis of tumor type and grade. However, there is limited benefit of the addition of HYbiopsy in the presence of definite diagnosis of grade 1–2 endometrioid tumors by OES.